2018
DOI: 10.1111/nyas.13864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammation on social processes and implications for health

Abstract: Although at first glance inflammation and social behavior may appear unrelated, research points to an important role for inflammation in shaping social processes. This review summarizes findings in this field, specifically highlighting work that provides support for the idea that inflammation can lead to (1) increases in sensitivity to negative, threatening social experiences and (2) increases in sensitivity to positive, socially rewarding experiences. These diverging sensitivities in response to inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 73 publications
1
33
0
1
Order By: Relevance
“…In all, these results contribute to a growing literature linking immunological processes and social behavior (e.g., Hennessy et al, ; Lopes, ; Moieni & Eisenberger, ). It is now well‐documented that social stimuli (potential mates, competitors, or offspring in need) can suppress sickness behaviors in infected animals in order to serve more immediate fitness purposes (Aubert et al, ; Lopes, Adelman, Wingfield, & Bentley, Adelman, Wingfield & Bentley, ; Yirmiya et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…In all, these results contribute to a growing literature linking immunological processes and social behavior (e.g., Hennessy et al, ; Lopes, ; Moieni & Eisenberger, ). It is now well‐documented that social stimuli (potential mates, competitors, or offspring in need) can suppress sickness behaviors in infected animals in order to serve more immediate fitness purposes (Aubert et al, ; Lopes, Adelman, Wingfield, & Bentley, Adelman, Wingfield & Bentley, ; Yirmiya et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, the reward task used in this study involved money and was inherently nonsocial. Our group has found that neural sensitivity to reward in response to inflammation varies between nonsocial and social forms of reward (7,30,32,47). Thus, the findings in this study might not extend to other forms of reward, particularly those that are social in nature.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies indicate a greater sensitivity of women to stressful and inflammatory conditions, for instance systemic inflammation impairs mood and affective behavior in women more than men (Moieni et al, ); also women seem to exhibit more robust stress responses and more potent immune responses compared to men (Bekhbat & Neigh, ), and women show greater activation of the enzyme indole 2,3‐dioxygenase (IDO), which metabolizes tryptophan (Trp) through the kynurenine (Kyn) pathway, and increased levels of anxiogenic Trp catabolites (Trycats) following immune activation (Songtachalert et al, ). On the contrary, other studies have shown that men display greater sensitivity to stressful and inflammatory conditions: women resolve local inflammatory responses more rapidly than men (Rathod et al, ), social isolation causes more mortality in men mediated by greater immune activation (Moieni & Eisenberger, ), and adult men seem to respond to typical psychological stressors with a greater increase in cortisol compared to age‐matched women (Kudielka, Buske‐Kirschbaum, Hellhammer, & Kirschbaum, ). Meanwhile, a meta‐analysis failed to observe any significant differences between men and women in how acute psychological stress affects inflammatory markers (Steptoe, Hamer, & Chida, ).…”
Section: Sex Differences In Rates Of Depression and Anxietymentioning
confidence: 96%